(untitled) (Research, Society and Development, 2020)
The concern for quality, nutritious, and safe food has increased in recent years and increasingly gaining ground in the food industries and research institutes around the world. In this context, cereal bars appear, which is a nutritious food of sweet and pleasant taste, source of vitamins, fiber, proteins, caloric source and complex carbohydrates. The fruits of the marizeiro (Geoffroea spinosa) by composition are considered good sources of proteins and sugars and low lipid content that generates energy value reduction, contributing to food formulations with caloric reduction. The aim of this research was to obtain mesocarp and almond meal from the fruit of the Marizeiro (Geoffroea spinosa), for the production of cereal bars determining their microbiological and physico-chemical profile in order to provide the product with an innovative character, different from what is found commercially. The flour produced was coded as almond flour (FA), mesocarpal flour (FM) and mixed flour (FMI). After processing, the flour was analyzed in terms of its physico-chemical and microbiological characteristics. All results of the microbiological analyses are in accordance with the standards established by the Technical Regulation of Resolution DRC n° 12. In the physical-chemical characterization all the contents are within the constant standards in the Brazilian legislation.